PERUBAHAN FUNGSI KOGNITIF PADA PASIEN PASCA CEDERA KEPALA DENGAN INTERVENSI STIMKOG - Made Ayu Wedariani, Lyna Soertidewi, Silvia Francisna Lumempouw, Herqutanto (Neurona Majalah Kedokteran Neuro Sains, 2013)
INTRODUCTION COMPUTER INSTRUMENT STIMULASI KOGNITIF STIMKOG IS ONE OF EXTERNAL THERAPEUTIC INTERVENTION WHICH CAN BE APPLIED TO MULTIDOMAIN COGNITIVE FUNCTION DISORDER AS FOUNDED IN PATIENT WITH TRAUMATIC BRAIN INJURY